An analytical study of the thinking compass model of the unit officials and the scouting stages - Sami Elias, Lamia; Sabri Mohammed Ali, Khansaa (International Journal of Psychosocial Rehabilitation, 2020)
The thinking compass scale is one of the best and most flexible diagnostic tools with which it is possible to identify a person’s way of thinking, and thus his behavior. This model is used to help individuals and institutions increase productivity, motivate workers, and accurately identify work specifications, employees, creativity and creative thinking. Hence the problem of this research came as the two researchers sought to use the thinking compass to know the way people think about the people’s officials and the scouting stages in the directorates of sports activity in order to put the hand around the pitfalls in their way of performance by changing the pattern of the brain and thus we can develop appropriate solutions for a successful performance and raise their level Practical. As Hermann’s theory mentioned that there are different languages for the brain in the way a person thinks according to the type of the brain, Hermann indicated that the brain pattern of each person can change if he has an urgent need for it, and the officials can learn according to the brain pattern that dominates each one of them, and the patterns Respond according to their thinking direction. As for the research goals, they were: Applying a scale that compasses thinking on officials of the people and the scouting stages, Analyzing the work of the people’s officials and the scouting stages through the thinking compass scale and knowing the difference between males and females in the management method .It is postulated that there are no statistically significant differences in the thinking compass scale for officials of the people and the scouting stages.